Toxicity and Anti-promastigote Activity of Benzoxazinoid Analogs Against Leishmania (Viannia) braziliensis and Leishmania (Leishmania) infantum - Gilberto de Sousa; William Gustavo Lima; Flávio José dos Santos; Francisco A. Macías; José María González Molinillo; Rafael Gonçalves Teixeira-Neto; João Máximo de Siqueira; Eduardo Sérgio da Silva (Tabriz University of Medical Sciences, 2020)
Purpose: Here, we aim to evaluate the antileishmanial activity of compounds with a benzoxazinoid (BX) skeleton, previously synthesized by our group, against Leishmania (Viannia) braziliensis and Leishmania (Leishmania) infantum promastigotes. Methods: Anti-promastigote activity, as well as cytotoxicity, were determined using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) colorimetric assays. The selectivity index (SI) for each compound was calculated using a ratio of the cytotoxicity of compounds and the geometric mean (GM) of antileishmanial concentrations to each species tested. The comparisons between groups were carried out using a t test or analysis of variance (one-way ANOVA). A P value of less than 0.05 was considered significant. Results: All the compounds tested were active, with IC50 falling between 92±6.19 µg/mL and 238±6.57 µg/mL for L. braziliensis, and 89±6.43 µg/mL and 188±3.58 µg/mL against L. infantum. Bex2, Bex3, Pyr1, Pyr2, and Pyr4 were compounds that showed activity similar to the drug Glucantime®, exhibited low cytotoxicity against splenic hamster cells (CC50 raging between >400 and 105.7±2.26 µg/mL) and had favorable selectivity indices (SI 1.12 to 3.96). Conclusion: The analogs in question are promising prototypes for the pharmaceutical development of novel, safer and more effective leishmanicidal agents.